SIFAT TERMAL, ELEKTROKIMIA DAN STRUKTUR MIKRO OKSIDA PEROVSKIT GANDA SEBAGAI MATERIAL KATODA SOFC BEROPERASI PADA SUHU MENENGAH - Subardi Adi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
The oxides SmBa0.8Sr0.2Co2O5+δ (SBSC) have been explored as cathode materials for IT-SOFCs using SDC as the electrolyte. XRD was used to determine the structure of SBSC powder, and SEM was used to observe the morphology of the microstructure. Thermogravimetric Analysis (TGA) is used to measure the change in amount and rate in weight of SBSC cathode powder as a function of temperature in a controlled atmosphere. Symmetrical cells were tested using a potentiostat Voltalab PGZ 301. The weight loss of SBSC oxide during the heating temperature range between room temperature and 800 oC was 0.003%. Electrochemical impedance spectroscopy (EIS), low field (LF), and high field (HF) approaches are used to obtain activation energy (Ea) values of 99.77 kJ mol-1, 70.26 kJ mol-1, and 73.10 kJ mol-1. The Ea of polarization resistance (Rp) for the SBSC cathode reaches 104.59 kJ mol-1. The well-connected cathode-electrolyte contact determines the low resistance, and the SBSC cathode particle size is consistently dispersed in the interval of 1-1.5 µm.